2012
DOI: 10.1002/asia.201201027
|View full text |Cite
|
Sign up to set email alerts
|

NIR Mega‐Stokes Fluorophores for Bioorthogonal Labeling and Energy Transfer Systems–An Efficient Quencher for Daunomycin

Abstract: A set of new azide- and alkyne-bearing lepidinium-based fluorophores were synthesized for bioorthogonal labeling schemes. These fluorescent dyes all show large Stokes-shifts with emission maxima in the near-infrared (NIR) region of the electromagnetic spectrum. The applicability of these dyes in the construction of energy-transfer systems was tested using one of these new fluorescent tags and daunomycin (Dau), an anticancer drug with fluorescent features. These daunomycin conjugates are the very first examples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Another common issue in fluorescent imaging techniques, especially in FRET applications is the small Stokes-shift of the probes. Kele and co-workers [67,68] synthesized a series of dyes with large Stokes-shifts based on a stilbene motif ( Figure 9). The labels were furnished with alkyne and/or azide as a bioorthogonal functionality and their emission ranged from 630 nm to 805 nm, covering the spectra from the red to the NIR regime.…”
Section: Bioorthogonally Applicable Small Green Red and Nir Emittinmentioning
confidence: 99%
“…Another common issue in fluorescent imaging techniques, especially in FRET applications is the small Stokes-shift of the probes. Kele and co-workers [67,68] synthesized a series of dyes with large Stokes-shifts based on a stilbene motif ( Figure 9). The labels were furnished with alkyne and/or azide as a bioorthogonal functionality and their emission ranged from 630 nm to 805 nm, covering the spectra from the red to the NIR regime.…”
Section: Bioorthogonally Applicable Small Green Red and Nir Emittinmentioning
confidence: 99%
“…In general, residues of the dimer side product 4 can be observed when using lower proportions of 4-methylquinoline and 1,3-diiodopropane. Even by heating, which usually takes up to 18-20 hours based on reported methods, the reaction mixture does not necessarily prevent the formation of any by-products [10][11][12]. Furthermore, we found that the total yield can considerably be enhanced by adding extra equimolar amounts of the starting materials to the filtrate.…”
Section: Scheme 1 Preparation Of 1-(3-iodopropyl)-4-methylquinolin-1mentioning
confidence: 84%
“…In the design process we aimed to develop bioorthogonally conjugatable, polarity sensitive labels with polar characteristics in order to minimize the possibility of nonspecific sticking to hydrophobic surfaces. As a starting point, we used frameworks (Figure ) that we formerly found amenable to conjugation mediated fluorescence turn on. , It was hypothesized that replacement of the lepidinium core of dyes 1a , b with more polar ethyl-benzothiazolium unit ( 2a , b ) would substantially increase polarity.…”
Section: Resultsmentioning
confidence: 99%